A rare case of factor Xii deficiency in a pregnant woman - Arimuthu, Durga Arinandini; Lim, Christopher Thiam Seong (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Factor XII deficiency, also known as the Hageman factor, is a rare disorder that has not been associated with any adverse outcomes. It is an interesting blood disorder whereby in the state of deficiency, it causes prolongation activated partial thromboplastin time (aPTT) which is correctable with mixing test. Although there have been case reports that have mentioned events of thrombosis and bleeding, however, no clear causal relationship has been established. Evidence for adverse events occurring in patients with Factor XII deficiency is sparse. We report here a case of a lady with a history of miscarriages who was incidentally found to have Factor XII deficiency during a routine workup for prolonged aPTT.